Preservice educators' and noneducators' knowledge and perceptions of responsibility about dyslexia. (29th January 2020) - White, Jennifer; Mather, Nancy; Kirkpatrick, Jennifer
Abstract : More individuals are affected by dyslexia than any other learning disability. The success of students with dyslexia receiving early identification and evidence‐based interventions is dependent upon the knowledge and skills of the school practitioners responsible for their academic programmes. This study investigated knowledge of dyslexia and perceptions of responsibility by administering the Knowledge and Insights of Dyslexia Survey ( KIDS ) to 243 university students. Survey responses of students ( n ) majoring in degrees in education (education majors [EM], n = 154) were compared with the responses of students majoring in degrees in architecture (noneducation majors [NEM], n = 89). In addition, the results were further examined between students majoring in General Education, Special Education, and School Psychology. Results indicated no significant differences in knowledge existed between EM and NEM or within EM. Of the topics investigated, participants knew the least about the treatment of dyslexia and demonstrated confusion about the components of appropriate instruction. Analysis of participant definitions revealed pervasive confusion about the characteristics of dyslexia with most believing myths that those with dyslexia "see and read backwards." Additionally, EM rated themselves as being moderately responsible for educating students with dyslexia and believed special educators hold the greatest level of responsibility.